2009
DOI: 10.1007/s10600-009-9355-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid, tocopherol, and sterol content of three Teucrium species from Tunisia

Abstract: In the present study analyses concerning the composition of vitamin E, sterols, triglycerides, and fatty acids of three Teucrium species (Teucrium alopecurus, T. nabli, and T. polium) seed oil were performed. Linoleic, linolenic, and palmitic were the major fatty acids. The oil was characterized by a high amount of phytosterol, wherein clerosterol, sitosterol, and stigmasterol are the main constituents. The amount of tocopherol is nearly 550 mg/kg of oil, with α-tocopherol as the major isomer. Information conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Fontana et al (1999) reported also the isolation of 6′-fatty acid esters of (24S)-24-ethylcholesta-5,25-dien-3-yl-glucopyranoside from T. fruticans. GC analyses of the sterol isolated from T. polium, T. nabli, and T. alopecurus seed oil showed the presence of four Δ5 sterols (campesterol, stigmasterol, clerosterol, sitosterol), wherein the sterol marker was clerosterol, which comprised 44.3, 47, and 58.9%, respectively in T. nabli, T. polium, and T. alopecurus of the total sterol content, followed by stigmasterol and sitosterol, which percentages are different according to the species (Hachicha et al, 2009). Teucrium seed oil is a rich source of phytosterol, with the highest concentration of 363.6 mg/100 g of oil in T. nabli, 330.4 mg/100 g of oil in T. polium, and 349.7 mg/100 g in T. alopecurus.…”
Section: Phytosterols and Tocopherolsmentioning
confidence: 98%
See 1 more Smart Citation
“…Fontana et al (1999) reported also the isolation of 6′-fatty acid esters of (24S)-24-ethylcholesta-5,25-dien-3-yl-glucopyranoside from T. fruticans. GC analyses of the sterol isolated from T. polium, T. nabli, and T. alopecurus seed oil showed the presence of four Δ5 sterols (campesterol, stigmasterol, clerosterol, sitosterol), wherein the sterol marker was clerosterol, which comprised 44.3, 47, and 58.9%, respectively in T. nabli, T. polium, and T. alopecurus of the total sterol content, followed by stigmasterol and sitosterol, which percentages are different according to the species (Hachicha et al, 2009). Teucrium seed oil is a rich source of phytosterol, with the highest concentration of 363.6 mg/100 g of oil in T. nabli, 330.4 mg/100 g of oil in T. polium, and 349.7 mg/100 g in T. alopecurus.…”
Section: Phytosterols and Tocopherolsmentioning
confidence: 98%
“…Teucrium genus is found everywhere in the world but mainly in the Mediterranean basin with 220 taxa (Greuter et al, 1986;Hachicha et al, 2009), 19 of which grow in Tunisia (Ghrabi et al, 1989). It has been used for more than 2000 years as halophytic medicinal herb considering their multiple properties: antispasmodic, hypolipidemic, anti-inflammatory, and hypoglycemic (Cavaleiro et al, 2004;Ricci et al, 2005).…”
Section: Lamiaceaementioning
confidence: 99%
“…Our SCE Extracts exhibited highest TEAC L-ORAC value when compared with Teucrium species seed oil of which ranged between 14.58 and 296mg/kg (Hachicha et al, 2009).…”
Section: L-orac Assay Resultsmentioning
confidence: 84%
“…In humans, the Tocopherols act mainly as Vitamin E precursors and they have some role in the prevention of some chronic diseases and certain cancers, and found mainly in leaves and seeds (Hachicha et al, 2009). Tocopherol contents of the SCE extracts as (α, β, γ, δ) (μg tocopherol/g DWE) from tow Algerian AI (BEJ and BBA) are given in Table 2, α-tocopherol dominated the profile in both AI, at 3290 ± 0.27 and 1580 ± 0.03 μg/g DWE respectively, while β-tocopherol is the lowest and was only 150 μg/g DWE detected in AI extracts.…”
Section: Results and Discussion Tocopherol Contents Of Sce Extractsmentioning
confidence: 99%
“…To the best of our knowledge, only one study covering determination of phytosterols in Teucrium species was published. The seed oil of three Teucrium species (T. alopecurus, T. nabli, and T. polium) were analyzed by Hachicha et al [33] and it was characterized by a high amount of phytosterol fraction, wherein clerosterol, sitosterol, and stigmasterol were the main constituents. Phytosterols have been used as blood cholesterol-lowering agents for more than 50 years, since they inhibit cholesterol absorption in the small intestine.…”
Section: Resultsmentioning
confidence: 99%